Ferumoxytol-enhanced magnetic resonance imaging in acute myocarditis. Issue 4 (6th October 2017) - Stirrat, Colin G; Alam, Shirjel R; MacGillivray, Thomas J; Gray, Calum D; Dweck, Marc R; Dibb, Kevin; Spath, Nick; Payne, John R; Prasad, Sanjay K; Gardner, Roy S; Mirsadraee, Saeed; Henriksen, Peter A; et al.
Abstract : Objectives: Ultrasmall superparamagnetic particles of iron oxide (USPIO)-enhanced MRI can detect tissue-resident macrophage activity and identify cellular inflammation within tissues. We hypothesised that USPIO-enhanced MRI would provide a non-invasive imaging technique that would improve the diagnosis and management of patients with acute myocarditis. Methods: Ten volunteers and 14 patients with suspected acute myocarditis underwent T2, T2* and late gadolinium enhancement (LGE) 3T MRI, with further T2* imaging at 24 hours after USPIO (ferumoxytol, 4 mg/kg) infusion, at baseline and 3 months. Myocardial oedema and USPIO enhancement were determined within areas of LGE as well as throughout the myocardium. Results: Myocarditis was confirmed in nine of the 14 suspected cases of myocarditis. There was greater myocardial oedema in regions of LGE in patients with myocarditis when compared with healthy volunteer myocardium (T2 value, 57.1±5.3 vs 46.7±1.6 ms, p<0.0001). There was no demonstrable difference in USPIO enhancement between patients and volunteers even within regions displaying LGE (change in R2*, 35.0±15.0 vs 37.2±9.6 s −1, p>0.05). Imaging after 3 months in patients with myocarditis revealed a reduction in volume of LGE, a reduction in oedema measures within regions displaying LGE and improvement in ejection fraction (mean −19.7 mL, 95% CI (−0.5 to −40.0)), −5.8 ms (−0.9 to −10.7) and +6% (0.5% to 11.5%), respectively, p<0.05 for all). Conclusion: In patients with acute myocarditis, USPIO-enhanced MRI does not provide additional clinically relevant information to LGE and T2 mapping MRI. This suggests that tissue-resident macrophages do not provide a substantial contribution to the myocardial inflammation in this condition. Clinical trial registration NCT02319278 ; Results.